Особливості інституціоналізації українського енергоринку та їх вплив на цінову політику у паливно-енергетичному комплексі - Пономарьов, С. В. (НТУ "ХПІ", 2013)
У статті виявлено причинно-наслідкові зв’язки між особливостями інституціоналізації вітчизняного енергоринку та ціновою політикою у паливно-енергетичному комплексі. Розкрито механізм їх деструктивного впливу на підвищення енергоефективності.

The article discovers cause and effect relationship between distinctive features of institutionalization of the domestic power market and the price policy in the fuel and energy complex as well as the mechanism of their destructive influence on the increase in power efficiency
Distinctive features of institutionalization of ukrainian power market and their influence on the price policy in the fuel and energy complex
Keywords: енергоринок; інституціоналізація; цінова політика; енергоефективність; ПЕК; power market; institutionalization; fuel and energy complex; price policy; power efficiency